The nexus between Islamic social finance, quality of human resource, governance, and poverty - Widiastuti, Tika; Mawardi, Imron; Siti Zulaikha; Sri Herianingrum; Robani, Anidah; Al Mustofa, Muhammad Ubaidillah; Atiya, Nikmatul (Elsevier Ltd, 2022)
This research aims to examine the effects of the Islamic social finance (zakat), the Islamic Human Development Index (IHDI), and the quality of governance on poverty alleviation in 39 Organization of Islamic Cooperation (OIC) member countries from 2007 to 2020. This study uses a fixed effect model to analyze the relationship between variables. The findings show that the Islamic human development index, as a proxy for the quality of human resources, supports the reduction of poverty in OIC countries. Furthermore, the zakat, voice and accountability, and trade openness have a negative and significant relationship with poverty. The quality of governance, population, inflation, and exchange rate, on the other hand, has no significant effect on the poverty rate. These findings can be used as the foundation for state government as the policymaker to solve poverty. The uniqueness of this study is the application of the modified human development index based on the five Islamic objectives and empirically investigates its impact on poverty.